Analisis Business Model Canvas pada Bisnis Creative Package di Industri Kreatif Digital - Lubis, Muhammad Anggi; Banyubasa, Apik; Kuntari, Wien (Universitas Maritim AMNI Semarang, 2024)
The Business Model Canvas (BMC) is a crucial tool for mapping out strategic components of a business. This paper examines the application of BMC in the creative package business within the digital creative industry. The study aims to understand how value propositions, customer segmentation, revenue streams, and other elements interact to drive innovation and competitiveness. Using qualitative methods, including literature reviews and case studies, the research identifies key insights for optimizing BMC elements to improve business performance in this sector. The findings highlight the importance of continuous adaptation to market trends and leveraging digital platforms for marketing and distribution.